2019
DOI: 10.3102/0002831219868182
|View full text |Cite
|
Sign up to set email alerts
|

Do Schools Reduce or Exacerbate Inequality? How the Associations Between Student Achievement and Achievement Growth Influence Our Understanding of the Role of Schooling

Abstract: This article explores how the associations between student achievement and achievement growth influence our understanding of the role schools play in academic inequality. Using nationally representative data from the Early Childhood Longitudinal Study, Kindergarten Class of 2010–2011 (ECLS-K:2011), we constructed parallel growth and lagged score models within both seasonal learning and school effects frameworks to study how student- and school-level socioeconomic and racial/ethnic backgrounds relate to student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 101 publications
(158 reference statements)
1
45
0
Order By: Relevance
“…In their widely influential work based on the nationally representative Early Childhood Longitudinal Study (ECLS, Kindergarten Cohort of 1998-1999, Downey et al (2004) showed that disparities in reading and math performance development grew faster during the summer compared to the rest of the school year. More recent U.S. studies that re-analyze ECLS and BSS data as well as analyzing new ECLS cohort data (e.g., Dumont and Ready 2019;Hippel and Hamrock 2019;Quinn et al 2016), report more nuanced results where schools do play a compensatory role but SES-related inequality in learning rates is smaller than reported by previous studies and not consistent across grades in elementary education.…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…In their widely influential work based on the nationally representative Early Childhood Longitudinal Study (ECLS, Kindergarten Cohort of 1998-1999, Downey et al (2004) showed that disparities in reading and math performance development grew faster during the summer compared to the rest of the school year. More recent U.S. studies that re-analyze ECLS and BSS data as well as analyzing new ECLS cohort data (e.g., Dumont and Ready 2019;Hippel and Hamrock 2019;Quinn et al 2016), report more nuanced results where schools do play a compensatory role but SES-related inequality in learning rates is smaller than reported by previous studies and not consistent across grades in elementary education.…”
mentioning
confidence: 81%
“…From this strand, scholars have portrayed schools as balancing inequalities. From the strand of research on school compositional effects, which investigates the effects of stratification across schools and teaching practices, schools have been portrayed as a source of inequality (Dumont and Ready 2019). To a certain extent, the conflicting views of these scholarly strands on the role of schools in educational inequality can be explained by the different counterfactual frameworks in which these research strands operate.…”
mentioning
confidence: 99%
See 3 more Smart Citations